Corporate social responsibility in the context of institutional and organizational change in the Colombian financial sector (2019)
This article aims first to review literature of different papers and authors about Corporate Social Responsibility in order to integrate the most representative viewpoints from the analysis’ diverse perspectives; second, to characterize how banking organizations in understand; and third, to describe the role that banks have in the Colombian society which is characterized by multiple social problems and where the financial sector, particularly the banking system, has been obtaining the most profits for several consecutive years.